The effect of using animation media on learning outcomes of budget plans at harapan mekar vocational high school Medan - Baginda Harahap; Adek Saputra; Debi Masri (Journal of Intelligent Decision Support System (IDSS), 2023)
The purpose of this study is to determine the effect the use of animated media in student learning outcomes in planned subjects determines budget growth (RAB) and student learning outcomes in Class XI Engineering Drawing Technology at SMK Harapan Mekar Medan. Based on research, the average peer group learning outcomes before the test was 46.54 and the average score after the test was 64.04; in the experimental class, the average before the test was 48.39 and the average after the test was 74.82. The learning outcomes of the comparison class increased by 17.50 and that of the test class by 26.43. The analysis uses all posttest results and is tested by t-test, obtained tcount > ttable (4.775 > 2.021) which shows that Ho is rejected and Ha is accepted. From these results it can be concluded that student learning outcomes using animation media are better than student learning outcomes using traditional methods (blackboard).